Predictors and Outcomes of Hematoma Expansion and Neurological Decline in Intracerebral Hemorrhage: A Multisite Mobile Stroke Unit Study - Asish K. Gulati; Tianwen Ma; Isaiah Rolle; Ryan Peterson; Bianca Pirlog; Justine Chen; Megan Heckathorn; Jonathan Ratcliff; Nicolas Bianchi; Carol Fleming; Michael Frankel; James Grotta; et al. (Stroke: Vascular and Interventional Neurology)
Background Hemorrhagic stroke, particularly intracerebral hemorrhage, is one of the leading causes of permanent disability worldwide. Early hematoma expansion (HE) is a key factor in neurological deterioration (ND) and functional outcomes post intracerebral hemorrhage. This observational cohort study examines the predictors and outcomes of HE and ND in spontaneous intracerebral hemorrhage patients using data from 3 Mobile Stroke Units (MSUs) in the United States. Methods Patients diagnosed with spontaneous intracerebral hemorrhage within 4 hours of last known well were included. Data collection involved initial and follow‐up non‐contrast (computerized tomography) CT scans from MSUs and emergency departments, from which the rate of HE and ND were determined. The interrater reliability for radiographic signs of HE was also assessed. Predictive factors were analyzed using multiple logistic regression models. Results Of the 55 patients who met the inclusion criteria, 27% experienced HE within the first 4 hours from last known well with the majority of HE occurring within the first 60 to120 minutes. Significant predictors of HE were a history of diabetes and blend sign on initial MSU CT scans. Predictors of ND included initial hematoma volume and the presence of hydrocephalus. Patients with HE and ND had a higher discharge modified‐Rankin Scale score and mortality rates. Interrater agreement on radiographic signs of HE varied, with moderate agreement on some signs and little to none on others. Conclusion Highest HE was seen within 60 to120 minutes from last known well for patients between MSU and emergency department transport. The blend sign and a history of diabetes emerged as key predictors of HE, whereas initial hematoma volume and hydrocephalus were significant for ND. Interventions to prevent HE and ND should be tested on the MSU in future studies.